Analysis of Indonesian Language Learning Difficulties in Upper Grade Elementary School Students: A Case Study at Agape Christian Elementary School Nabire - Jasmari, Jasmari; Telussa, Rivaldo Paul; Umpel, Refly J (Universitas Pattimura, 2026)
This study aims to analyze the forms of Indonesian language learning difficulties experienced by 4th and 6th grade students in elementary school. The method used is qualitative research with a case study approach. The research subjects were 12 students from grades 4 and 6 at Agape Christian Elementary School Nabire, selected through purposive sampling. Data collection techniques were carried out through observation, in-depth interviews, and documentation. Data analysis used the interactive model of Miles and Huberman consisting of data reduction, data presentation, and conclusion drawing. The results showed that Indonesian language learning difficulties experienced by students include: (1) difficulty in reading comprehension of complex texts, (2) difficulty in writing essays with coherent and cohesive structures, (3) low mastery of standard vocabulary, and (4) difficulty in understanding effective sentence structures. Contributing factors come from internal factors (low reading interest, habit of using regional languages at home) and external factors (less varied teaching methods and limited learning media). The implications of this research are expected to serve as a reference for teachers in designing more effective and innovative Indonesian language learning strategies in upper grade elementary schools.